Sex differences in suicidal behaviors and aggression in US Veterans. (July 2021) - McGlade, Erin; Bueler, Elliott; DiMuzio, Jennifer; Sheth, Chandni; Legarreta, Margaret; Yurgelun-Todd, Deborah
Abstract: Female Veterans are the fastest growing demographic group in the Department of Veterans Affairs. Moreover, suicide rates in female Veterans are increasing, making suicide in female Veterans a topic of vital clinical and research significance. The current study examined the association between suicide, aggression, and mood symptoms by sex. Participants consisted of 264 Veterans (female=54, male=210) ages 18-55. Veterans completed well-validated measures of suicidal behaviors, aggression, anxiety, and depression. Male Veterans reported higher physical aggression, verbal aggression, anger, hostility, and total aggression compared to female Veterans. In male Veterans, lifetime suicidal behavior including ideation and attempts was correlated with total aggression and subscales of physical aggression, verbal aggression, anger, and hostility. However, in female Veterans lifetime suicidal behavior was significantly associated with hostility and anger. There were no between-group differences in measures of suicidal behaviors, anxious or depressive symptoms. These results suggest important differences in the association between aggression and suicidal behavior by sex. These data have significant clinical implications, as males with aggressive traits and females who endorse hostility and anger may be more likely to engage in suicidal behaviors.